Perancangan Jasa Produksi Video Digital Komersial 64Visual Sebagai Media Promosi Startup Bisnis di Surabaya - Leonard Merlim; Rendy Iswanto (Jurnal Vicidi, 2019)
Indonesia's rapid economic growth makes the emergence of many startup businesses. The development of the business makes competition in the business more tight. Many brands are competing to create a unique and attractive promotion so that their businesses can survive in the industry. The digital era has made it even easier for brands to promote their goods so that they reach the eyes and ears of audiences. This study aims to determine the importance of using video media as a primary promotional tool for the Surabaya brand. The research method used was a qualitative method with interviews and questionnaires. The results showed that Instagram video media greatly boosted the company's overall income.